2021
DOI: 10.1021/jacs.0c08926
|View full text |Cite
|
Sign up to set email alerts
|

Optical Control of Cannabinoid Receptor 2-Mediated Ca2+ Release Enabled by Synthesis of Photoswitchable Probes

Abstract: Cannabinoid receptor 2 (CB2) is a promising target for the treatment of neuroinflammation and other diseases. However, a lack of understanding of its complex signaling in cells and tissues complicates the therapeutic exploitation of CB2 as a drug target. We show for the first time that benchmark CB2 agonist HU308 increases cytosolic Ca2+ levels in AtT-20­(CB2) cells via CB2 and phospholipase C. The synthesis of photoswitchable derivatives of HU308 from the common building block 3-OTf-HU308 enables optical cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 63 publications
0
45
0
4
Order By: Relevance
“…Despite recent setbacks, 27 emergent clinical applications of hydrophobic molecules, such as cannabinoids, have garnered renewed interest in their effective delivery. 28 It was recently demonstrated that rationally-designed polymers can overcome the delivery challenges of hydrophobic small molecules by, for example, forming nanodroplets that can carry these molecules into the cytosol. 13 These custom polymers are melts at room temperature, with glass transition temperatures > 150 °C lower than that of PU-PEG, and are not co-drawable with structural polymers typically used in fiber drawing of neural probes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite recent setbacks, 27 emergent clinical applications of hydrophobic molecules, such as cannabinoids, have garnered renewed interest in their effective delivery. 28 It was recently demonstrated that rationally-designed polymers can overcome the delivery challenges of hydrophobic small molecules by, for example, forming nanodroplets that can carry these molecules into the cytosol. 13 These custom polymers are melts at room temperature, with glass transition temperatures > 150 °C lower than that of PU-PEG, and are not co-drawable with structural polymers typically used in fiber drawing of neural probes.…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the mechanism through which H308 modulates vascular tone through the CB 2 receptor. A study carried out in a cell line with high expression of the CB 2 receptor showed that HU308 increases cytosolic calcium by two mechanisms: one acting at the level of reservoirs such as sarcoplasmic reticulum increasing the release of calcium, and another by activation of calcium channels in the cell membrane mediated by G coupled receptors (Gαq/11), and phospholipase C (PLC) way [49]. These mechanisms that increase the availability of cytosolic calcium could be responsible for the vasoconstriction effect of HU308 observed in our experiments, and if this mechanism were responsible, then the decrease in the expression of CB 2 receptors shown in this study (Figure 5b) could be associated with the reduction of vasoconstriction observed in the aorta of rats treated with ZnONPs.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, there is a single nanosystem that enables sustained 1 O 2 generation and sufficient oxygen supply during the fPDT process by alternatively applying PDT and PTT regulated by two NIR laser beams. Dual-light irradiation can provide more controllability and has recently been widely used in multiple biological and biomedical fields, such as cancer treatment, [21] antibacterial, [40] photopharmacology, [41] optogenetics, [42] and optical-control of protein function and signaling, [43][44][45] etc. Moreover, the replacement of the dark cycle of conventional fPDT with PTT further enhanced the overall outcome of the anticancer phototherapy due to the synergistic effect of PDT and PTT (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%